2018
DOI: 10.15576/asp.fc/2018.17.3.119
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of Sediment Carried During Flood Events in a Small Urban Catchment

Abstract: The aim of this study is to present results of investigations into rainfall-runoff-suspended sediment transport process, based on field measurements conducted in small (A = 28.7 km 2) urban catchment of Służew Creek, located in Warsaw. Hydrological monitoring was carried out by the Department of Hydraulic Engineering at the WULS-SGGW (Warsaw University of Life Sciences). Between 2014-2017, twelve flood events were recorded, during which rainfall, discharge, turbidity, and suspended sediment concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…The influence of several extreme rainfall events on very high suspended solids concentration and load in small rivers was also noted by Tramblay et al [47]. During 12 rainfall-induced floods in the small basin of the Sluzew Creek located in Warsaw (A = 28.7 km 2 ), the maximum suspended solids concentration varied from 102 to 429 g•m −3 and was several dozen times higher than the annual average [29]. In turn, Old et al [48] found that the suspended solids concentration during a specific rainfall increased almost 100-fold within 15 min (from 14 to 1360 mg•L −1 ).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The influence of several extreme rainfall events on very high suspended solids concentration and load in small rivers was also noted by Tramblay et al [47]. During 12 rainfall-induced floods in the small basin of the Sluzew Creek located in Warsaw (A = 28.7 km 2 ), the maximum suspended solids concentration varied from 102 to 429 g•m −3 and was several dozen times higher than the annual average [29]. In turn, Old et al [48] found that the suspended solids concentration during a specific rainfall increased almost 100-fold within 15 min (from 14 to 1360 mg•L −1 ).…”
Section: Discussionsupporting
confidence: 58%
“…During both analysed rainfall events (21 and 25 July) in the Silnica sub-catchments with a high proportion of impervious areas, the first flush effect was observed. A similar phenomenon, of the rapid increase in suspended solids concentration and the occurrence of its maximum value before the culmination of the flood wave in small watercourses, has been documented many times [22,29,[53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Fine-grained soils dominate the watershed area. Previous investigations conducted in the Służew Creek catchment were related to urban hydrology with a focus on flood flow estimation [33,34] and operation of small detention ponds for flood and sediment load reduction [35,36] or sediment transport [37,38]. The climate in Poland is continental and in the case of the analyzed study site it may be described as moderate.…”
Section: Characteristics Of the Study Catchmentsmentioning
confidence: 99%
“…The equipment used for taking SS samples did not allowed us to take any samples during the night time. This may have limitations in case of storm events occurring during the night time (Krajewski et al 2018) and is discussed further in sect. 5.…”
Section: Field Investigationsmentioning
confidence: 99%